Impairments in testicular function indices in male wistar rats: a possible mechanism for infertility induction by Xylopia aethiopica fruit extract - Adienbo, Ologhaguo Macstephen; Nwafor, Arthur; Dapper, Datonye Victor (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The accumulating evidence about alterations in male fertility necessitates the need to screen more medicinal plants for their effect on male reproductive functions. This study is aimed at evaluating the effects of fruit extract of Xylopia aethiopica on testicular functions in males using wistar rats as models. Methods: Forty eight adult male rats, randomly divided into four groups of 12 each, were used for the study. Group 1 (control), while groups 2, 3 and 4 (test groups). Daily oral doses of 0.5, 2.0 and 10.0 mg/kg b.w. of hydro-methanol extract were given to the test groups for 30 days followed by 30 days withdrawal. From each group, 6 animals were sacrificed on days 31 and 61 of the study and samples collected: Testes and epididymis were each weighed; blood was assayed for serum testosterone; testes processed for tissue biochemical studies. Results: Results show significant (P <0.05) reductions in the weight of reproductive organs, serum testosterone; testicular glycogen, cholesterol, protein and malondialdehyde; while testicular superoxide dismutaase increased. Conclusions: It was concluded that Xylopia aethiopica impairs testicular functions in rats and therefore fertility in males.